2004
DOI: 10.1007/s00432-004-0610-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and cyclin D1 are independently amplified and overexpressed in esophageal squamous cell carcinoma

Abstract: Frequent overexpression and gene amplification of EGFR and CCND1 make these molecules and their pathways potential therapeutic targets for ESCC. In addition, EGFR and CCND1 appeared to be independently altered suggesting alternative mechanisms for pathway activation. Therapeutic agents targeting these molecules are urged to be tested in clinical trials and comprehensive biological analyses should be included to properly interpret the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 24 publications
7
72
1
Order By: Relevance
“…We totally agree with them about the fact that several analyses of HER2 carried out by immunohistochemistry or other methods (Shiga et al, 1993;Hardwick et al, 1997;Tanaka et al, 1997;Friess et al, 1999;Wang et al, 1999;Akatmatsu et al, 2003;Miyazono et al, 2004;Mimura et al, 2005a, b;Sato et al, 2005;Sunpaweravong et al, 2005) have all found rates of overexpression greater than 2.8%. To our opinion, the differences observed between these different studies have several origins: the first of them, as clearly said by Khan and coworkers is the high heterogeneity in the methodologies used in the collection of studies cited by these authors.…”
supporting
confidence: 83%
“…We totally agree with them about the fact that several analyses of HER2 carried out by immunohistochemistry or other methods (Shiga et al, 1993;Hardwick et al, 1997;Tanaka et al, 1997;Friess et al, 1999;Wang et al, 1999;Akatmatsu et al, 2003;Miyazono et al, 2004;Mimura et al, 2005a, b;Sato et al, 2005;Sunpaweravong et al, 2005) have all found rates of overexpression greater than 2.8%. To our opinion, the differences observed between these different studies have several origins: the first of them, as clearly said by Khan and coworkers is the high heterogeneity in the methodologies used in the collection of studies cited by these authors.…”
supporting
confidence: 83%
“…This result was the high-end of the data in literature showing HER-2 expression in oesophageal SCC varying between 0 and 31% (Sunpaweravong et al, 2005), in which the different rate of HER-2 expression seems to be due to the different criteria for evaluating the results. Importantly, both EGFR-and HER-2-positive tumours were observed in 18% of all patients, out of which 75% showed EGFR and HER-2 expression in individually distinct regions.…”
Section: Discussionmentioning
confidence: 49%
“…INK4a (40%-50%) tumor suppressor genes, and human telomerase (hTERT) activation (Mandard et al 2000;Metzger et al 2004;Sunpaweravong et al 2005). Cyclin D1 and EGFR overexpression appears to be associated with early events in tumor initiation, in particular with preneoplastic (squamous dysplasia) and early neoplastic stages, whereas p53 and p16 inactivation is associated with tumor progression in advanced neoplastic stages (Mandard et al 2000;Okano et al 2003).…”
mentioning
confidence: 99%